The Internet in Everything: Freedom and Security in a World with No Off Switch - DeNardis, Laura (Yale University Press, 2020)
A compelling argument that the Internet of things threatens human rights and security and that suggests policy prescriptions to protect our future The Internet has leapt from human-facing display screens into the material objects all around us. In this so-called Internet of Things-connecting everything from cars to cardiac monitors to home appliances-there is no longer a meaningful distinction between physical and virtual worlds. Everything is connected. The social and economic benefits are tremendous, but there is a downside: an outage in cyberspace can result not only in a loss of communication but also potentially a loss of life. Control of this infrastructure has become a proxy for political power, since countries can easily reach across borders to disrupt real-world systems. Laura DeNardis argues that this diffusion of the Internet into the physical world radically escalates governance concerns around privacy, discrimination, human safety, democracy, and national security, and she offers new cyber-policy solutions. In her discussion, she makes visible the sinews of power already embedded in our technology and explores how hidden technical governance arrangements will become the constitution of our future.